2009
DOI: 10.1177/0040517509352527
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Structure of Monofilament PET Woven Fabrics and their UV Protection Properties

Abstract: The importance of protection against ultraviolet radiation (UV) is increasing daily. The dependence of the UV protection level on different clothes is determined by the shape and design of fabrics, and especially by their construction parameters. The fabric structure represents an important factor which is in most cases the only condition for good protection. Other possibilities to ensure good or even excellent protection, mainly by finishing treatments, can be efficient only if the fabric structure is closed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 5 publications
0
22
0
1
Order By: Relevance
“…These results are shown in Table 3. For further observation, we took into consideration only samples in plain weave, avoiding the small influence of twill weave on the values of K T , K R , and K A , as well as on the complexity in their presentation, in tables [5]. On the other hand, conclusions based on the samples in the plain weave were used in the model and showed that the steps are valid for the samples in the twill weave also.…”
Section: Results and Calculationsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results are shown in Table 3. For further observation, we took into consideration only samples in plain weave, avoiding the small influence of twill weave on the values of K T , K R , and K A , as well as on the complexity in their presentation, in tables [5]. On the other hand, conclusions based on the samples in the plain weave were used in the model and showed that the steps are valid for the samples in the twill weave also.…”
Section: Results and Calculationsmentioning
confidence: 99%
“…Many researchers have investigated the influence of different factors related to the textile materials used for UV protection. They have investigated the influence of type of material [1,2], fabric constructions [1,[3][4][5], colors, and different additives [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the textile fabrics themselves undergo limited UV-induced degradation, they still provide excellent UV protection [2]. Various investigations have pointed out the infl uence of clothing design [3,4], fabric construction (open porosity, weight, and thickness) [5][6][7][8][9][10][11][12][13], dyes, chemical agents or UV stabilizers applied to the fabric [10,[14][15][16][17][18], and type of fi bre [19][20][21] on UV protection properties. However, the porosity or tightness of the fabric is the dominant parameter in obtaining UV radiation protection, followed by the ability of fi bres to absorb UV radiation (UVR).…”
Section: Introductionmentioning
confidence: 99%
“…1). OF is a critical feature regarding the end-use performance that has to be taken into consideration in the fields of protection (Gabrijelcicet al 2009;Webster et al 2009;Dimitrovski et al 2010;Gotipamul et al 2014), end-use performance (Teli et al 2008;Akgun et al 2012), thermo-physiological comfort ( € Ozc¸elik et al 2007;Lee and Obendorf 2012;Kumar and Mitra 2013) and fabric hand (Naebe et al 2013). In the specialized literature, it is more usual to deal with OF complementary, the cover factor (i.e., the fraction of the web area covered by yarns) (Marks et al 1993).…”
Section: Introductionmentioning
confidence: 99%